PENGARUH KUALITAS DAGING AYAM TERHADAP KEPUASAN KONSUMEN PADA UD. ALAM SEMESTA MANDIRI SIBOLGA - Kaharuddin Kaharuddin; Fauziah Nur Simamora (Universitas Pahlawan Tuanku Tambusai, 2022)
One of the efforts made by entrepreneurs to increase customer satisfaction is to always keep chicken meat in high quality conditions. The purpose of this study was to determine whether there was an effect of chicken meat quality on consumer satisfaction at UD. Sibolga Independent Universe. The hypothesis in this study is: There is an Influence of Chicken Meat Quality on Consumers at UD. Sibolga Independent Universe. The type of research used in this research is a descriptive correlational research design. The total population of 375 samples in this study was 15% of (375 people), so that 56 people were obtained. Sources of data in this study are primary and secondary data. Analysis techniques are quantitative descriptive analysis techniques. To analyze the data using descriptive analysis and quantitative analysis. Results Based on the research, the relationship between chicken meat quality and consumer satisfaction was 0.752 categorized as strong. The effect of chicken meat quality on consumer satisfaction 56.5%. The obtained simple linear regression model, Y = 7,455 + 0,748X shows the relationship between chicken meat quality and consumer satisfaction in a positive direction. The hypothesis test is known that the value of tcount is greater than ttable 7,046 > 2,010, then Ho is rejected and Ha is accepted. This means that the proposed hypothesis can be accepted. Keyword: Quality of Chicken Meat, Consumer Goals.